Nutritional Status Association With Sarcopenia in Patients Undergoing Maintenance Hemodialysis Assessed by Nutritional Risk Index - Kurajoh, Masafumi; Mori, Katsuhito; Miyabe, Mizuki; Matsufuji, Shota; Ichii, Mitsuru; Morioka, Tomoaki; Kizu, Akane; Tsujimoto, Yoshihiro; Emoto, Masanori (Frontiers in Nutrition, 2022)
Background: Malnutrition and sarcopenia are frequently observed in patients undergoing maintenance hemodialysis (MHD). To elucidate whether malnutrition is associated with sarcopenia in those cases, the relationship of nutritional status with sarcopenia was investigated. Methods: Nutritional status was assessed using a nutritional risk index (NRI) developed for patients undergoing MHD. This retrospective cross-sectional study included 315 MHD patients (199 males, 116 females), who were divided into low-risk (score 0-7) and medium-/high-risk (score 8-13) groups. Sarcopenia and severe sarcopenia, along with low muscle mass, low muscle strength, and low physical performance were defined using the Asian Working Group for Sarcopenia 2019 criteria. Results: The median NRI score was 5.0, while the prevalence of medium-/high-risk cases among the patients was 31.1%. Additionally, the rates of those with low muscle mass, low muscle strength, and low physical performance were 55.9%, 60.6%, and 31.4%, respectively, while those of sarcopenia and severe sarcopenia were 44.1% and 20.0%, respectively. Multivariable logistic regression analyses revealed a significant (p<0.001) association of NRI score with sarcopenia [odds ratio (OR) 1.255, 95% confidence interval (CI) 1.143-1.377] and severe sarcopenia (OR 1.257, 95% CI 1.122-1.407), as well as low muscle mass (OR 1.260, 95% CI 1.157-1.374), low muscle strength (OR 1.310, 95% CI 1.178-1.457), and low physical performance (OR 1.216, 95% CI 1.104-1.339). Furthermore, medium-/high-risk status showed a significant (p<0.05) association with sarcopenia (OR 2.960, 95% CI 1.623-5.401) and severe sarcopenia (OR 2.241, 95% CI 1.151-4.362), as well as low muscle mass (OR 2.141, 95% CI 1.219-3.760), low muscle strength (OR 7.665, 95% CI 3.438-17.091), and low physical performance (OR 2.570, 95% CI 1.401-4.716). Conclusions: These results suggest that malnutrition contributes to sarcopenia/severe sarcopenia in MHD patients by reducing muscle mass and strength, and physical performance.